Pengaruh Rasio Solvabilitas, Likuiditas, Profitabilitas Terhadap Nilai Saham Perusahaan (Kebijakan Dividen Sebagai Variabel Moderating) Pada Perusahaan Manufaktur Di BEI Tahun 2017- 2021 - Anggraini, Refinna; Zulkifli, Makhmud (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The purpose of this study was to determine the effect of liquidity solvency and profitability on the value of company shares with dividend policy as a moderating variable in manufacturing companies listed on the Indonesian stock exchange for the 2017- 2021 period. The population selected was the food and beverage sub-sector of 30 companies, the sample was selected using the purposive sampling method, as many as 17 companies were the sample in the study. The variables used in this study are solvency, liquidity and profitability as independent variables, the company's stock value as the dependent variable, dividend policy as a moderating variable. Testing the research hypothesis using multiple linear analysis techniques with SPSS (statistical product and service solutions) application tools. The results of this study prove that: (1) Solvability has a positive and significant effect on the company's share value, (2) The dividend policy is able to moderate the effect of solvency on the company's share value, (3) Liquidity has a negative and insignificant effect on the company's share value, (4) Dividend policy is able to moderate the influence of liquidity on the company's stock value, (5) Profitability has a positive and significant effect on company value, (6) Dividend policy is able to moderate the effect of profitability on company stock value